PRAME immunohistochemistry compared to traditional FISH testing in spitzoid neoplasms and other difficult to diagnose melanocytic neoplasms - Warbasse, Elizabeth; Mehregan, Darius; Utz, Sarah; Stansfield, R. Brent; Abrams, Judith (Frontiers in Medicine, 2023)
PRAME (PReferentially expressed Antigen in Melanoma) is a gene first identified in melanoma. It has been proposed as a useful marker to differentiate melanoma from benign melanocytic neoplasms. Recently genomic testing using fluorescence in situ hybridization has been used to aid in the diagnosis of difficult melanocytic neoplasms. We have compared PRAME staining to FISH testing results in 83 difficult to classify melanocytic neoplasms which showed spitzoid histologic features. A relatively low sensitivity of 29.6% and high specificity of 76.8% is seen with PRAME staining as compared to genomic testing with fluorescence in situ hybridization. This study highlights the limitations of PRAME staining in spitzoid neoplasms.